The service quality of computer laboratory's facility in FTMSK : student's satisfaction / Mazliani Arsad - Arsad, Mazliani (2006)
This research is conducted in purpose to find out student satisfaction level towards the quality of computer lab's facility service which provided by FTMSK. The sample size used in this research is 168 respondents consist of students at all faculties at city campus. The level of student satisfaction was measured using IFMA Standardized Users Satisfactory Survey which from model SERVQUAL adaptation. According to the model, this research analyzes the student satisfaction in using the services of computer lab's facility according to three dimension which is availability and arrangement of equipment, size and capacity and safety and cleanliness of computer lab. To fulfill the specification of goal and objective in the research, data has been analysis through questionnaires method. The higher mean score for the dimension safety and cleanliness in lecture room shows the average level only. Beside that, dimension of availability and arrangement equipment and the size and computer lab capacity dimension also get average mean score too. On the whole, the result of the study shows that the level of student satisfaction is moderately satisfied with the service facility of computer lab. As a conclusion, the FTMSK has to structure an action plan to overcome current problem and take effective steps in increasing the level of customer satisfaction.